THE INFLUENCE OF WORK MOTIVATION, JOB SATISFACTION AND ORGANIZATIONAL CULTURE ON TEACHER PERFORMANCE AT SMK NEGERI 1 LHOKSEUMAWE - Said Afif Nabil; Aiyub Yahya; Em Yusuf Iis; Faisal Matriadi (RADJA PUBLIKA, 2024)
This research aims to determine the influence of work motivation, job satisfaction and organizational culture on teacher performance at SMK Negeri 1 Lhokseumawe. It appears that there are still many complaints from teachers who are less involved in student achievement, and some teachers want better compensation or improvements to the work environment. and teachers also feel that the policy is inadequate. Such communication patterns that are limited to formal hierarchies can limit the flow of innovative ideas. The independent variables in this research are work motivation, job satisfaction and organizational culture. Meanwhile, the dependent variable is teacher performance. This type of research uses quantitative methods. Data was collected using a questionnaire containing questions and statements by distributing it to teachers at SMK Negeri 1 Lhokseumawe The assessment technique uses a Likert scale. This research was conducted on a sample of 90 teachers at SMK Negeri 1 Lhokseumawe. The sampling technique used census or saturated samples. This research uses multiple linear regression analysis with the SPSS (Statistical Program for Social Science) program. The research results show that work motivation and job satisfaction have a positive effect on teacher performance, while organizational culture does not have a significant impact as shown by teachers at SMK Negeri 1 Lhokseumawe